The Tomato lncRNA47258-miR319b-TCP Module in Biocontrol Bacteria Sneb821 Induced Plants Resistance to Meloidogyne incognita - Fan Yang; Xiaoxiao Wu; Lijie Chen; Mingfang Qi (Pathogens)
Long non-coding RNAs (lncRNAs) represent a class of non-coding RNAs. In the study of Pseudomonas putida Sneb821-induced tomato resistance to Meloidogyne incognita, reverse transcription polymerase chain reaction (RT-PCR) was employed to validate 12 lncRNAs in tomato. Among them, the lncRNA47258/miR319b/TCP molecular regulatory module was likely implicated in the process of Sneb821-induced tomato resistance against M. incognita. Through the application of tomato hairy root and virus-induced gene silencing (VIGS) technologies for the investigation of lncRNA47258, it was determined that lncRNA47258 could target the TCP (Solyc07g062681.1) gene and modulate the metabolic pathway of tomato jasmonic acid-related indices, thereby impeding the infection of M. incognita. Moreover, the overexpression of the target gene TCP (Solyc07g062681.1) using tomato hairy root technology demonstrated that it could regulate the jasmonic acid synthesis pathway in tomato, consequently obstructing the infection and suppressing the development of M. incognita. Collectively, lncRNA47258/miR319b/TCP (Solyc07g062681.1) was preliminarily verified to be involved in the Sneb821-induced resistance process against M. incognita in tomato.